Perceptions of the benefits and challenges of the role of advanced practice nurses in nurse‐led out‐of‐hours care in Hong Kong: a questionnaire study. Issue 7 (2nd August 2012) - Christiansen, Angela; Vernon, Veronica; Jinks, Annette
<x xml:space="preserve">Abstract</x> Aims and objectives. The aim of the study was to identify the factors that nurses perceive may facilitate or hinder the development of advanced practice nurse roles in Hong Kong. Background. Advanced practice nurses are increasingly prominent in nurse‐led out‐of‐hours care in Hong Kong in response to changes to junior doctors' hours of work. Setting. Three five‐day workshops for Hong Kong‐based advanced practice nurses were offered in partnership with UK clinicians. The aim of the workshops was to share UK experiences of implementation of the 'Hospital at Night' model of care delivery. The questionnaire study undertaken was not part of the workshop programme. However, the workshops gave the authors a unique opportunity to access relatively large numbers of Hong Kong‐based advanced practice nurses. Participants. The workshops were attended by experienced nurses who had been or were about to be appointed as advanced practice nurses. All nurses who attended one of the three workshops (n = 120) agreed to participate in the study. Methods. Responses to two open questions posed in the questionnaire were the subject of a content analysis. Results. A prominent finding of the study was that respondents viewed the benefits of introducing advanced practice nurse roles in Hong Kong as outweighing any challenges. One of the main features of the perceived benefits relates to improving the quality and safety of patient care. The greatest challenges associated with the role related to acceptance of the role by other healthcare professionals, and difficulties associated with the general public's traditional attitudes to healthcare provision in Hong Kong. Conclusions. Education of the public concerning the implementation of such roles is of crucial importance. Relevance to clinical practice. Findings from this study enhance understanding of the factors that hinder or facilitate advanced practice roles in out‐of‐hours care in Hong Kong.